(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article deals with the study of the human brain, how the system of the human brain works, its performance, how the performance is measured. The system of measurement and the unit of measurement in other objects and other systems are given. The analysis of the control process is carried out, depending on the object or process, on the basis of which, on the basis of the information obtained, an algorithm and control software are developed. The temporary development of the algorithm and control software Ta, Ta is determined less than the control time Tcon. The algorithms are developed in a real-time system.